2018
DOI: 10.1007/s10096-018-3299-2
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal vaginal microbioma is associated with severity of localized provoked vulvodynia. Role of aerobic vaginitis and Candida in the pathogenesis of vulvodynia

Abstract: Localized provoked vulvodynia (LPV) causes introital dyspareunia in up to 14% of premenopausal women. Vaginal infections like candidosis may play a initiating role. The aim of this study was to test a possible association of vaginal microbiota alternations such as Candida vaginitis (CV), aerobic vaginitis (AV) and bacterial vaginosis (BV) with severity of vulvodynia and painful intercourse. In an observational study, Q-tip touch test (score 1 (no pain) to 10 (worst possible pain)) was performed on seven vestib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Considering the close correlation between inflammation and bacteria, one of the current avenue of research in VVS pathogenesis is focused on the analysis of vaginal microbiome. In our previous study, we have demonstrated that vaginal microbiome is altered in women with VVS [10], and other studies have sug- [11,[25][26][27].…”
Section: Discussionmentioning
confidence: 88%
“…Considering the close correlation between inflammation and bacteria, one of the current avenue of research in VVS pathogenesis is focused on the analysis of vaginal microbiome. In our previous study, we have demonstrated that vaginal microbiome is altered in women with VVS [10], and other studies have sug- [11,[25][26][27].…”
Section: Discussionmentioning
confidence: 88%
“…This nding is consistent with Reed et al [1], who found that more than one-third of women diagnosed with vulvodynia were treated for candidiasis before receiving the nal diagnosis and presented no improvement in vulvar symptoms. A possible explanation for the large number of women treated for candidiasis before reaching the nal diagnosis also relies on the pathogenesis of vulvodynia that associates a high prevalence of yeast infections preceding VVD diagnosis [18]. However, it is important to consider that a large number of women might be diagnosed with candidiasis when complaining of vulvodynia symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Patients have stated that they feel dirty and bad, were ashamed of their condition and avoided sexual intercourse [17]. In another study carried out Donders and colleagues, it was stated that abnormal vaginal microbiome caused vulvodynia, the most frequent cause was bacterial vaginosis, and this in turn caused sexual dysfunction in patients [18].…”
Section: Discussionmentioning
confidence: 99%